Influence of light-dark cycle on delayed recovery from isoflurane anesthesia induced by hypnotics in mice - Atsunobu Sugano; Hiroki Murai; Syunpei Horiguchi; Yuma Yoshimoto; Yuki Amano; Tomoki Kimura; Yoshinori Iba (Elsevier, 2021)
We previously reported that brotizolam, but not suvorexant, delayed recovery from isoflurane anesthesia in mice. However, the effects of hypnotics may be altered by the circadian rhythm. Locomotor activity was measured using sighted (ICR and C57BL/6J) and blind (FVB/N and C3H/HeN) mice, and the effects of hypnotics on isoflurane anesthesia were compared during the light and dark periods. In sighted mice, recovery induced by brotizolam was delayed in the light period, while that by suvorexant was delayed in the dark period. In C57BL/6J mice, delayed recovery induced by brotizolam was marked, and that by suvorexant was observed in the light and dark periods. Locomotor activity was low in the last 6 h of the dark period in blind mice, and was similar to that in the light period. In blind mice, delayed recovery induced by brotizolam was identical in both periods, while suvorexant did not influence recovery from isoflurane anesthesia. These results suggest that the effects of hypnotics on isoflurane anesthesia are altered by the circadian rhythm and that daily light-dark stimuli may be required for the chronopharmacological effects of hypnotics.